Investigation of veterinary service delivery and service providers on dairy cattle farms in central Ethiopia - Kebede, G.; Moje, N.; Shafi, A.; Kassahun, R.; Merera, O.; Leta, S.; Waktole, H.; Megersa, B.; Amenu, Kebede (BioMed Central, 2025)
Background: Livestock diseases are major constraints affecting the productivity, health and welfare of animals in dairy sectors in Ethiopia. The prevalence of animal diseases and inadequate animal health services are key barriers to improving animal productivity and health. Studies assessing animal health delivery in Ethiopia are limited.